THE RELATIONSHIP BETWEEN RELIGIOUS UNDERSTANDING AND WASTE MANAGEMENT BEHAVIOR AMONG MUSLIM COMMUNITIES IN MEDAN - Ikhwan Kurnia Hutasuhut; Khatibah; Wahyu Rizky Parmanda; Hilda Syahrani (TASAMUH : Jurnal Komunikasi dan Pengembangan Masyarakat Islam, 2026)
This study examines the relationship between religious understanding and waste management behavior among Muslim communities in Medan City. Using a qualitative case study in Medan Tembung District, data were collected through observation, in-depth interviews, and documentation involving religious leaders, academics, government officials, waste-bank managers, and residents. The findings show that the community generally understands environmental care as part of Islamic teaching: cleanliness is associated with faith, environmental protection with religious obligation, and humans with khalifah fil ardh entrusted to maintain ecological balance. However, this understanding has not been fully reflected in daily practice. Waste segregation remains limited, improper disposal persists, and participation in community-based waste management is weak. This gap is shaped by entrenched habits, limited facilities, weak institutional support, and insufficient internalization of ecological values. Strengthening eco-religious literacy and collaboration among religious institutions, government, and local communities is therefore essential.